АҒАРТЫЎШЫ БАБАМЫЗДЫҢ БИЙБАҲА МИЙРАСЫ - Диланов, Б.Г. (FAN va JAMIYAT, 2024)
This article talks about Jadids, who emerged from among the intelligentsia in Central Asia at the beginning of the 20th century, who started the movement to awaken love for our historical culture in the minds of people, and who were the main initiators of this movement. At the same time, Seyfulgabit Majitov, who made a significant contribution to the development of Karakalpak science, created the first textbooks, wrote a number of prose, poetic and dramatic works, and his services in the formation of Karakalpak writing and spelling rules, were analyzed.